Influence of the double bond position in combustion chemistry of methyl butene isomers: A shock tube and laser absorption study. Issue 11 (24th June 2020) - Arafin, Farhan; Laich, Andrew; Ninnemann, Erik; Greene, Robert; Rahman, Ramees K.; Vasu, Subith S.
Abstract: Shock tube experiments have been carried out on 2‐methyl‐1‐butene (2M1B), 2‐methyl‐2‐butene (2M2B), and 3‐methyl‐1‐butene (3M1B)—the three isomers of methyl butene compound. Carbon monoxide (CO) time‐histories and ignition delay times are obtained behind reflected shockwaves over the temperature range of 1350‐1630 K and pressures of 8.3‐10.5 atm with stoichiometric mixtures of 0.075% fuel in O2 /Ar. Comparative ignition study reveals that 3M1B ignites significantly faster than the other two isomers, while 2M1B dissociates earlier but ignites later than 2M2B. Possible mechanisms for this behavior are discussed with ignition delay time sensitivity and reaction path analysis. In addition, time‐resolved CO measurements are compared with three different reaction mechanisms from the literature. Sensitivity analyses have been carried out to identify important reactions that need attention to accurately predict the chemistry of these isomers. Further investigation into the rates of unimolecular fuel decomposition reactions and C3 H3 + O2 = CH2 CO + HCO reaction are suggested based on the current investigation.